A transdisciplinary approach to managing emerging and resurging mosquito-borne diseases in the Western Pacific region - Hardy, Margaret C.; Barrington, Dani J. (MDPI, 2017)
Mosquitoes transmit a number of harmful diseases that have an impact on local communities and visitors, and many pose a threat to neighboring countries. As federal monitoring budgets shrink across the world, the increasing importance of citizen scientists in monitoring and identifying invasive species, as well as acting to prevent these diseases, are discussed. Examples of past mosquito management programs are provided, and future directions are discussed with an emphasis on the Western Pacific Region.
Keywords: citizen science; mosquitoes; vector-borne disease; participatory action; WaSH; Zika; Western Pacific